2013
DOI: 10.1038/onc.2013.42
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR-486-5p contributes to tumor progression and metastasis by targeting protumorigenic ARHGAP5 in lung cancer

Abstract: We have previously shown that miR-486-5p is one of the most downregulated micro RNAs in lung cancer. The objective of the study was to investigate the role of miR-486-5p in the progression and metastasis of non-small-cell lung cancer (NSCLC). We evaluated miR-486-5p expression status on 76 frozen and 33 formalin-fixed paraffin-embedded tissues of NSCLC by quantitative reverse transcriptase PCR to determine its clinicopathologic significance. We then performed function analysis of miR-486-5p to determine its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
204
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(218 citation statements)
references
References 31 publications
13
204
1
Order By: Relevance
“…In addition, miR-216b, miR-186, miR-337-3p and miR-760 were found to cooperatively promote cellular senescence through the p53-p21 (Cip1/ WAF1) pathway in human colorectal cancer cells (75). Given that the overexpression of miR-486-5p is closely correlated with the downregulated expression of ARHGAP5 in lung tumor tissues, which considerably inhibits lung cancer cell migration and invasion, miR-486-5p may act as a tumor suppressor contributing to the progression and metastasis of non-small cell lung cancer (76). Actually, the biological processes including cell proliferation, invasion, growth and metastasis in which miR-216b and miR-486-5p are involved are closely related to the development of drug resistance in cancers (49,77), and the annotation of biological processes also suggests that cell proliferation and growth are associated with drug resistance.…”
Section: Microrna-mrna Prediction Tool ------------------------------mentioning
confidence: 99%
“…In addition, miR-216b, miR-186, miR-337-3p and miR-760 were found to cooperatively promote cellular senescence through the p53-p21 (Cip1/ WAF1) pathway in human colorectal cancer cells (75). Given that the overexpression of miR-486-5p is closely correlated with the downregulated expression of ARHGAP5 in lung tumor tissues, which considerably inhibits lung cancer cell migration and invasion, miR-486-5p may act as a tumor suppressor contributing to the progression and metastasis of non-small cell lung cancer (76). Actually, the biological processes including cell proliferation, invasion, growth and metastasis in which miR-216b and miR-486-5p are involved are closely related to the development of drug resistance in cancers (49,77), and the annotation of biological processes also suggests that cell proliferation and growth are associated with drug resistance.…”
Section: Microrna-mrna Prediction Tool ------------------------------mentioning
confidence: 99%
“…Previous studies demonstrated the importance of miRNAs during the development, classification, diagnosis and prognosis of CRC (7)(8)(9). miR-486-5p has been reported to function as a tumor suppressor in various types of cancer, including non-small-cell lung (10) and primary gastric cancer (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, miR-451 is involved in mediating the resistance of breast cancer cells to the chemotherapeutic drug doxorubicin through regulating MDR1 expression (21). Aberrant expression of miR-486-5p is a frequent molecular event that has important functions in human malignances (22,23); however, evidence of biological roles for miR-451 and miR-486 in relapsed/refractory AML has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%